Formation of a system of requirements for ensuring information security at critical information infrastructure facilities in cooperation between the Russian Federation and the People’s Republic of China on the example of the Power of Siberia gas pipeline - A. R. Semishkur; I. I. Livshits (Вестник Дагестанского государственного технического университета: Технические науки)
Objective. The purpose of the study is an analytical review of the legislation for the formation of a system of requirements for ensuring and controlling information security at critical information infrastructure facilities in cooperation between the Russian Federation and the People’s Republic of China.Method. Reviewed using various benchmarking methods - historical, socio-cultural, legal to find similarities and differences in the approaches of partner countries on the issue of Critical Information Infrastructure.Result. Proposals have been made to improve Russian legislation regarding the management of information security at critical information infrastructure facilities.Conclusion. The direction of this study is very relevant and requires further development of organizational and technical measures to implement the requirements of legal documents on the protection of information at special-purpose informatization objects.